Florida Darkwinged Subterranean Termite, Amitermes floridensis Scheffrahn, Su, and Mangold (Insecta: Isoptera: Termitidae: Termitinae) - Rudolf H. Scheffrahn; Nan-Yao Su (EDIS)
This document is EENY-112, one of a series of the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date August 1999. Reviewed May 2003.